War Lord : a novel - Cornwell, Bernard (Cornwell, Bernard. Last kingdom, 2020)
"The final installment in Bernard Cornwell's bestselling Saxon Tales series, chronicling the epic story of the making of England. England is under attack. Chaos reigns. Northumbria, the last kingdom, is threatened by armies from all sides, by land and sea, and only one man stands in their way. Torn between loyalty and sworn oaths, the warrior king Lord Uhtred of Bebbanburg faces his greatest ever battle - and prepares for his ultimate fate."--Publisher's description.